The application of innovative teaching techniques as a good policy to reduce the attrition rate at university - Inglada-Pérez, Lucía; Soto, Oliver; Tovar, Edmundo (Revista de Evaluación de Programas y Políticas Públicas, 2013)
In this paper we study how the application of new innovative teaching techniques in our school, has produced an overall improvement in the performance of students along the school years 2005-2008. Students with a worse previous level of student achievement in highschool have not only increased their performance but also the school attrition rate has lowered. Thus, we prove that policies focusing on improving student performance can be successful to increase in the long run the deficit of students. Resumen En el presente estudio se estudia el impacto de la aplicación de nuevas técnicas innovativas en la educación de los estudiantes de la Universidad Politécnica de Madrid durante los años 2005–2008. Los resultados son muy esperanzadores. No sólo se ha conseguido una mejora en el rendimiento de los alumnos sino que la tasa de suspensos haya disminuido considerablemente. La práctica que se propone constituye una buena opción para incrementar el déficit de alumnos y mejorar el rendimiento de los mismos.